Analysis of the Current Status and Influencing Factors of Social Alienation in Adolescent Scoliosis Patients - Yi Zeng; Qin Fu; Xia Li (Orthopaedic Surgery, 2025)
ABSTRACT Objective Adolescent scoliosis patients frequently experience social alienation, yet comprehensive studies addressing its determinants in China remain scarce. This study aims to understand the current status of social alienation in adolescent scoliosis patients and analyze its influencing factors to inform targeted interventions. Methods A cross‐sectional study was conducted from January 2022 to December 2023. A total of 252 adolescent scoliosis patients were investigated using the General Information Questionnaire, Social Alienation Scale, Family Care Scale, and Anxiety Self‐Rating Scale. Multivariate linear regression analysis was employed to identify independent factors influencing social alienation. Results Adolescent patients with scoliosis experience significant social isolation (37.21 ± 0.78), lower levels of family care (6.33 ± 0.70), and higher anxiety self‐assessment scores (53.11 ± 0.88), and the results showed that education level, per capita monthly family income, time of disease onset, type of scoliosis, Cobb's angle, ability to take care of oneself, appearance deformation, family care, and anxiety were found to independently influence the social alienation score (all p < 0.05). Conclusion Adolescent patients with scoliosis exhibit a heightened degree of social isolation due to a variety of factors. Healthcare professionals should focus on providing individualized interventions, particularly for those with lower levels of education and family support, to alleviate their social isolation.